The relationship between spirituality and sexual variety seeking between Iranian students in Malaysia - Sani, Mandana Daneshi; Wan Jaafar, Wan Marzuki; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of the present study is to investigate the relationship between sexual variety-seeking factors and spiritual awareness among a sample of Iranian students who were selected randomly for the present study. Measurement tools included SVS (sexual variety seeking) and SAI (spirituality assessment inventory). This research included 3 hypotheses; of which 1 was accepted with moderate significant relationship and 2 were accepted with weak significant relationship. The findings indicate that there exists a negative association between spiritual awareness and sexual variety seeking in behaviour which means spirituality can reduce the desire for sexual variety seeking between the behaviours of men towards sexual variety. However, there is not a significant relationship between seeking sexual variety and intimacy seeking in relationships.